KONTRIBUSI PENDAPATAN USAHATANI TOGA TERHADAP PENDAPATAN KELUARGA DI DESA MEKAR BHUANA, KECAMATAN ABIANSEMAL KABUPATEN BADUNG - Genoveva Sarina Adung; Dian Tariningsih; Ida Ayu Made Dwi Susanti; Ni Putu Anglila Amaral (Fakultas Pertanian dan Bisnis Universitas Mahasaraswati Denpasar, 2022)
Family medicinal plants (TOGA) which include ginger, turmeric, galangal, temu lawak, are one of the people's choices to be planted in their yards with consideration because they can be used for health. The purpose of the study was to analyze the income, contribution and efficiency of TOGA farming in Mekar Bhuana Village, Abiansemal District, Badung Regency. The research was carried out from September to October 2021. The types of data used in this study were quantitative and qualitative data, while the data sources in this study were primary and secondary data. Respondents in the study amounted to 10 people. The methods of collection include observation, interviews, literature study and documentation. The results showed that the amount of TOGA farming income in Mekar Bhuana Village, Abiansemal District, Badung Regency per planting period for 7 months, expanding 19.1 acres of land was Rp. 350.701.or Rp. 1.836.130 per planting period per ha. The contribution of TOGA farm income to the total family income in Mekar Bhuana Village, Abiansemal District, Badung Regency is Rp. 350.701 (8,17%), while the efficiency of TOGA farming in Mekar Bhuana Village, Abiansemal District, Badung Regency is profitable and efficient to develop, so it can be suggested to farmers to continue developing TOGA cultivation, especially in Mekar Bhuana Village, Abiansemal District, Badung Regency. considering the contribution of TOGA farming to total family income is quite high and profitable